2004
DOI: 10.1097/00003727-200410000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Learning Public Health Nursing in Urban, Rural, and Border Counties of Texas

Abstract: A partnership between the 3 types of public health agencies present in South Texas was created to allow baccalaureate nursing students to increase their understanding of public health through clinical experiences in a city/county health department, a rural county health department, and a regional health department. The students assessed the health of a selected population, identified factors affecting the health of the selected population, gained skills in community participation and decision making, worked wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…More optimal FVC observed in rural areas compared to urban areas was a notable trend since many pieces of research have reported rural residents having significantly lower utilization of public health services across many developing countries [18,19]. We stipulated that the difference in service delivery mechanism between rural and urban areas might be the main reason for the disadvantage of vaccination service in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…More optimal FVC observed in rural areas compared to urban areas was a notable trend since many pieces of research have reported rural residents having significantly lower utilization of public health services across many developing countries [18,19]. We stipulated that the difference in service delivery mechanism between rural and urban areas might be the main reason for the disadvantage of vaccination service in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborations between more than two partners included: (1) a school of nursing that worked with three health departments to diversify students' public health clinical learning experiences (Reifsnider, Hook, Muennink, & Vogt, 2004) and (2) two schools of nursing, two tribal health agencies, and three county public health agencies that developed an academic practice partnership (Fauchald, 2004).…”
Section: Collaboration Examplesmentioning
confidence: 99%
“…Collaborative models between education and practice have also facilitated the development of population-based PHN competencies (Anderson et al, 2004;Kaiser & Rudolph, 2003;Reifsnider et al, 2004;Zahner & Gredig, 2005).…”
Section: Collaboration Examplesmentioning
confidence: 99%